The Influence Of Marketing Mix On Customer Loyalty Using Smart IB Savings Products - Nasution, Fathia Zuhra; Yanti, Nursantri; Inayah, Nurul (Jurnal Manajemen Bisnis, 2024)
The aim of this research is to find out whether customer loyalty to the Smart iB Savings product of Bank Sumut Kcp Syariah Karya is influenced by the Marketing Mix during the 2018–2023 period. Participants in this research were customers of Bank Sumut Kcp Syariah Karya. Quantitative research is the methodology used. Researchers only selected a sample of 33 customer respondents, so the selection was carried out using a saturated sampling technique. Validated and reliable questionnaires were included in the data collection methods. Multiple linear regression, classical assumption test, F hypothesis test, t hypothesis test, and coefficient of determination are data analysis methods used to answer hypotheses. The results of the research conducted show that the coefficient of determination (adjusted R square) is 0.663 or 66.3%. That Price, Product, Place and Promotion simultaneously influence the loyalty of customers who use the Smart iB Savings product at Bank Sumut Kcp Syariah Karya Period 2018-2023. Price has no effect on customer loyalty who use the Smart iB savings product at Bank Sumut Kcp Syariah Karya for the 2018-2023 period. The product influences the loyalty of customers who use the Smart iB savings product at Bank Sumut Kcp Syariah Karya for the 2018-2023 period. Place has no effect on customer loyalty who use the Smart iB savings product at Bank Sumut Kcp Syariah Karya for the 2018-2023 period. Furthermore, promotions have an effect on customer loyalty who use Smart iB savings products at Bank Sumut Kcp Syariah Karya for the 2018-2023 period.